2013
DOI: 10.1182/blood-2012-12-474585
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel sequencing, aCGH, and RNA-Seq technologies provide a comprehensive molecular diagnosis of Fanconi anemia

Abstract: • Application of capturing/ sequencing, copy number, and RNA analysis technologies ensures comprehensive molecular diagnosis of Fanconi anemia.Current methods for detecting mutations in Fanconi anemia (FA)-suspected patients are inefficient and often miss mutations. We have applied recent advances in DNA sequencing and genomic capture to the diagnosis of FA. Specifically, we used custom molecular inversion probes or TruSeq-enrichment oligos to capture and sequence FA and related genes, including introns, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 23 publications
4
93
0
3
Order By: Relevance
“…Indeed, massive parallel sequencing complemented with array comparative genomic hybridization and RNA sequencing analysis allowed the identification of biallelic germline mutations in different FA families (Chandrasekharappa et al. 2013). However, it has been shown that massively parallel sequencing techniques are feasible to identify CNV in FA and other diseases (Ameziane et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, massive parallel sequencing complemented with array comparative genomic hybridization and RNA sequencing analysis allowed the identification of biallelic germline mutations in different FA families (Chandrasekharappa et al. 2013). However, it has been shown that massively parallel sequencing techniques are feasible to identify CNV in FA and other diseases (Ameziane et al.…”
Section: Discussionmentioning
confidence: 99%
“…Massive parallel sequencing approaches have already been successfully used. 21,22 In our experience, we are validating the Ion PGM TM system (Life Technologies) and have identified mutations in 6 cases, including 2 belonging to group FA-C. Since preliminary data are very encouraging, we are confident to be able to apply this procedure not only in the routine of molecular screening in FA but also for re-sequencing those cases (3 in our experience) who, having been analyzed only partially, are still without a molecular diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Возможны несколько подходов. Первый -секвенирование экзо-ма, позволяет получить максимальный объем инфор-мации [61,62,65]. Второй подход подразумевает сек-венирование ограниченного числа интересующих и уже описанных в литературе генов (таргетное ресеквени-рование), список которых можно дополнять или мо-…”
Section: редкие болезниunclassified